Content Analysis of Responsibility Values in Islamic Religious Education Textbooks for Elementary Students - Yusnaili Budianti; Masganti Sit; Indah Purnamasari (Fitrah: Journal of Islamic Education, 2025)
Character education at the elementary school level plays a strategic role in shaping students’ moral awareness and attitudes, particularly the value of responsibility as a foundation of ethical behavior in Islam. However, empirical studies examining how the value of responsibility is represented in Islamic Religious Education textbooks remain limited. This study aims to systematically analyze the representation and alignment of responsibility values in elementary school Islamic Religious Education textbooks. Employing a qualitative approach with a content analysis design, this study examines textbooks for Grades 1, 2, and 3 used in the national curriculum. Data were analyzed through coding and categorization of responsibility values into personal, social, and ecological dimensions. The findings reveal that responsibility values are predominantly represented through personal and social dimensions, particularly in the form of habituation of religious practices, discipline, cleanliness, care for others, and role modeling of Islamic figures, while the ecological dimension of responsibility remains limited and unevenly distributed across grade levels. These findings indicate that textbooks function as important instruments for character formation but require stronger reflective approaches and a more balanced integration of responsibility dimensions. The implications of this study are relevant for curriculum development, textbook writing, and instructional practices in Islamic Religious Education that are more holistic and contextual.